'Am I a Vampire then, who Must have a Spike Driven into my Heart?' Monstrosity and the Gothic in Illness Narratives and Medical Advice Literature on Eating Disorders. Issue 1 (1st May 2015) - Michelis, Angelica
<x xml:space="preserve">Abstract</x> This article engages with the discourse of food and eating especially as related to the representation of the abject eating-disordered body. I will be particularly interested in the gothic representation of the anorexic and bulimic body in samples of medical advice literature and NHS websites and how they reinforce popular myths about anorexia by imagining the eating disordered body as a fixed object of abjection. Focusing on the use of gothic devices, tropes and narrative structure, these imaginations will be read against alternative representations of anorexic/bulimic bodies in autobiographical illness narratives, fictional accounts and a psychoanalytical case history in order to explore how gothic discourses can help opening up new understandings and conceptions of illness, healing and corporeality in the dialogue between medical staff and patients.